Lactylation in diabetes mellitus and its complications: mechanisms of action and therapeutic potential - recent advances - Zhou, Min; Liu, Lan; Sun, Yihong; Wang, Xiaoshu (Frontiers in Endocrinology, 2025)
BackgroundDiabetes mellitus (DM) and its complications represent a global health burden. Lactylation, a novel post-translational modification (PTM) linking metabolism to epigenetic regulation, has emerged as a key mediator in metabolic disorders.ObjectiveThis review systematically summarizes the regulatory roles and therapeutic potential of lactylation in DM pathogenesis and complications. Key Findings: (1) Lactylation modulates core diabetic pathways by targeting IRS-1 (promoting insulin resistance), NLRP3 (amplifying inflammation), and FOXO1 (enhance oxidative stress); (2) Tissue-specific regulation is observed in complications: lactylation of LARS1 and ACSF2 exacerbates podocyte injury and mitochondrial dysfunction in nephropathy; the FTO-CDK2 axis drives vascular anomalies in retinopathy; and H4K12 lactylation activates Foxo1-mediated oxidative stress in cognitive impairment.ConclusionLactylation functions as a critical metabolic-epigenetic hub, and targeting its “writer-eraser-reader” system may offer novel therapeutic strategies for DM and complications, requiring further clinical translation.